2013
DOI: 10.1098/rspb.2013.0189
|View full text |Cite
|
Sign up to set email alerts
|

Inferred L/M cone opsin polymorphism of ancestral tarsiers sheds dim light on the origin of anthropoid primates

Abstract: Tarsiers are small nocturnal primates with a long history of fuelling debate on the origin and evolution of anthropoid primates. Recently, the discovery of M and L opsin genes in two sister species, Tarsius bancanus (Bornean tarsier) and Tarsius syrichta (Philippine tarsier), respectively, was interpreted as evidence of an ancestral long-to-middle (L/M) opsin polymorphism, which, in turn, suggested a diurnal or cathemeral (arrhythmic) activity pattern. This view is compatible with the hypothesis that stem tars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…This hypothesis could account for both the high number of cones in the fovea of Tarisus (relative to Aotus ; Figure 1 ) and the phenomenon of lunar philia (increased activity under moonlight) among spectral tarsiers (Gursky, 2003b). It might also explain why the photoreceptors of tarsiers have attributes normally associated with mesopic or photopic light levels (Melin et al, 2013; Joffe et al, 2014). Taken together, the natural history of tarsiers represents a model system for studying how experience might shape the functional organization of the brain and the ensuing functional ecology of an animal.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis could account for both the high number of cones in the fovea of Tarisus (relative to Aotus ; Figure 1 ) and the phenomenon of lunar philia (increased activity under moonlight) among spectral tarsiers (Gursky, 2003b). It might also explain why the photoreceptors of tarsiers have attributes normally associated with mesopic or photopic light levels (Melin et al, 2013; Joffe et al, 2014). Taken together, the natural history of tarsiers represents a model system for studying how experience might shape the functional organization of the brain and the ensuing functional ecology of an animal.…”
Section: Discussionmentioning
confidence: 99%
“…This is often explained by the fact that the earliest niche occupied by mammals was a nocturnal one; since cones perform poorly under low-light conditions, the selection for their maintenance was relaxed (Jacobs 2008). Although, it is noteworthy that most recently Melin et al (2013) have suggested that the anthropoid visual system -including the L/M opsin gene -evolved under low-light conditions and challenges the perspective that while basal primates were nocturnal, stem anthropoids were diurnal (see "▶ Primate Origins and Supraordinal Relationships: Morphological Evidence," this handbook).…”
Section: Trichromatic Color Visionmentioning
confidence: 96%
“…Indeed this same group later demonstrated that amongst lemur species, the presence of M or L pigments is highly variable . The presence of trichromacy mediated by the same mechanism of polymorphic LWS genes in New World monkeys and different present-day species of the separate prosimian branches of tarsiers and strepsirhines suggests that the ancestral primate may have been a trichromat with polymorphic LWS genes (Melin et al, 2013b). Indeed when comparing the sequences of primate LWS genes, including several prosimian species, the most parsimonious conclusion is that the ancestral primate carried polymorphic copies of the LWS gene (Tan et al, 2005).…”
Section: Trichromacy In Prosimiansmentioning
confidence: 99%